Land use restrictions and household transportation choice - Mueller, Andrew G., author; Shields, Martin, advisor; Weiler, Stephan, advisor; Mushinski, David, committee member; Leisz, Stephen, committee member (Colorado State University. Libraries, 2016)
The primary objective of the dissertation is to further existing research on the link between the built environment and travel behavior. The dissertation proposes to make this advance in two distinct ways. First, by testing the impact of land use regulation on travel behavior by incorporating zoning restrictions as an exogenous variable in the model. Second, by explicitly modeling spatial variation in the discrete choice of mode of transportation. The dissertation is organized into three chapters. The first develops a multinomial discrete choice model that addresses unobserved travel preferences by incorporating sociodemographic, built environment, and land use restriction variables. The second builds upon the first by explicitly modeling spatial dependence of travel mode choice in a and compares the results of models from the first and second chapters to address the effect of spatial dependence on travel behavior-built environment model estimates. The third reviews previous models and theories related to land use restrictions, and reviews the economic and policy implications of findings from the first two chapters.
Keywords: mode choice; zoning; spatial econometrics; land use